Effect of market orientation and innovation on business performance: Mediating role of competitive advantage - Ullah, Habib (IIUC Business Review, 2022)
The goal of this study is to describe how market orientation and innovation help Small and Medium-Sized Enterprises (SMEs) in Bangladesh had improved their marketing performance. To do this, a sample of 350 managers and Operations Managers from SME Enterprises in Bangladesh was chosen by purposive sampling technique and studied using structural equation modeling (SEM). This research shows that SMEs' performance would improve if they identify and meet customer needs. Furthermore, a company's ability to build a competitive advantage based on innovation and market orientation is directly correlated to the degree to which the company places a high priority on its customers. The study also found that market orientation and innovation have substantial direct and indirect implications on business success through competitive advantage. This means that competitive advantage considerably moderates the effect of market orientation and innovation on marketing performance, suggesting that a stronger business performance is associated with improved competitive advantage. For business success, managers must invest in customer orientation and innovation performance. IIUC Business Review, Vol.-11, Issue-1, Dec. 2022, pp. 53-70